HUBUNGAN KEMAMPUAN KOMUNIKASI INTERPERSONAL DENGAN KUALITAS INTERAKSI SOSIAL PADA SISWA DI SMP NEGERI 7 MUARO JAMBI - Litasya, Zahara; Sutja, Akmal; Andi Yaksa, Rully (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the relationship between interpersonal communication skills and the quality of social interaction among ninth-grade students at SMP Negeri 7 Muaro Jambi. The study employed a quantitative approach with a correlational method. The population consisted of 198 students, with a sample of 132 students selected using the simple random sampling technique. Data were collected using questionnaires that had been tested for validity and reliability. Data analysis was conducted using the Pearson Product Moment correlation test with the assistance of IBM SPSS Statistics ver 22. The results showed that students' interpersonal communication skills were in the high category, with a percentage of 84.92%, while the level of social interaction was also in the high category, with a percentage of 79.45%. The correlation test results indicated a significance value of 0.000 < 0.05 and a correlation coefficient of 0.730. These findings indicate a positive and significant relationship between interpersonal communication skills and the quality of students' social interaction. The higher the students' interpersonal communication skills, the better their quality of social interaction.